FNIRS an emerging technology for design: advantages and disadvantages - Providencia, B (2022)
fNIRS is a functional neuroimaging technology that measures activations according to the oxygenation and deoxygenation of neural activities. A technique still little used within design, but that can contribute in neurodesign and affective, for example. Although emotions are universal, their way of perceiving and feeling is individual. The emotion design has some gaps, namely the lack of mastery of techniques and knowledge of human responses to emotions. In total, 44 articles were analyzed in a non-systematic way, with the aim to find the advantages and disadvantage of using fNIRS. As conclusion, it was possible to perceive that the fNIRS is a promising neuroimaging technique with 20 advantages points and 13 disadvantages points. The stimuli can be sensorial, cognitive and motor, handled in laboratory, in social environments or in real situations. fNIRS is already used in studies of emotions and can help to investigate the brain activations in the face of emotion processing and the affective design, enabling the possibility to design better experiences, products, services or environments focused on this affective parameter in front of neurocognition. fNIRS is an emerging and promising technique, which can help to understand some gaps in human beings as promote pleasure and well-being.